AB0254 PATIENT CHARACTERISTICS, COMORBIDITIES, AND INFECTION OUTCOMES AMONG RHEUMATOID ARTHRITIS (RA) PATIENTS IN PUERTO RICO (PR). (2nd June 2020) - Suryavanshi, M.; Suri, S.; Bao, Y.; Ruiz, M.; Patel, V.; Madera-Miranda, E.
Abstract : Background: Although the burden of comorbidities and infections in RA patients in the US is well established, 1 there is an evidence gap for RA patients in the US territory of PR. Objectives: To describe the patient demographics, clinical characteristics, and infection rates in patients with RA in PR Methods: A retrospective cohort of adults age ≥18 years from PR with ≥2 diagnosis of RA were identified using International Classification of disease codes (ICD-9 or ICD-10) on separate days from Jan 1, 2006 to June 30, 2018 using the Truven MarketScan™ database. Patients were divided into three treatment cohorts: no treatment, conventional disease-modifying anti-rheumatic drugs (csDMARD) user, and biologic DMARD (bDMARD) user. Patients in the no treatment group were followed from their first RA diagnosis date to the date of initiation of any DMARDs. The csDMARD users were followed from the initiation of csDMARD until the initiation of any bDMARD or targeted synthetic DMARDs (tsDMARDs). Patients were censored at the last observed medical claim if treatments were not initiated during follow-up. bDMARD users were followed from the date of initiation of bDMARD or tsDMARD until their last observed medical claim. Crude incidence rates /1000 person-years (PY) were reported for opportunistic infections (e.g. Mycobacterium, Cytomeglavirus, Candidiasis, and Chlamydial infections) and infections requiring hospitalisation. Results: Of the 623 patients in the cohort of RA patients from PR, majority were women (75.4%), aged 41-64 years (67.1%), employed full time (69.8%), with PPO health plan (89.4%), and with mean length of follow-up of 5.77 years from index RA diagnosis. Our results shows that cardiovascular conditions (CVD, hypertension, and hyperlipidemia) were the most prevalent comorbidities in PR patients with RA (Table 1 ), followed by diabetes (55.7%) in the total RA patient population. The crude IR/1000 PY for opportunistic infections was 23.35 for patients in the no treatment cohort, 48.52 for patients in csDMARD, and 28.31 for bDMARD users. For hospitalized infections, the crude IR/1000 PY was 26.00 for patients in the no treatment cohort, 22.08 for csDMARD users, and 41.90 for bDMARD users. Conclusion: Puerto Rican patients with RA have a significant burden of comorbidities, infections and hospitalisations. Trends indicate a variation in the burden by the type of treatment. Furthermore studies are warranted to better understand the potential healthcare implications of comorbidities in patients with RA. References: [1 ]Yun, Huifeng et al. "Comparative risk of hospitalised infection associated with biologic agents in rheumatoid arthritis patients enrolled in Medicare." Arthritis & Rheumatology 68, no. 1 (2016): 56-66. Disclosure of Interests: Manasi Suryavanshi Consultant of: Bristol Myers Squibb, Sonick Suri Consultant of: Bristol Myers Squibb, Ying Bao Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, Maribelis Ruiz Shareholder of: Bristol Myers Squibb, Employee of: Bristol Myers Squibb, Vardhaman PATEL Employee of: Bristol Myers Squibb, Eory Madera-Miranda Employee of: Bristol Myers Squibb